Redox cycling of sulfur via microbes in soil boosts the bioavailability of nutrients to Brassica napus - Rabia Aslam; Ghulam Jilani; Tajwar Alam; Zia–Ul -Haq; Ambreen Bhatti; Riaz Ullah; Iram Naz; Muhammad Ikram; Nida Fatima; Essam A. Ali; Muhammad Zahoor; Shah Zaman (PLoS ONE, 2025)
Deficiency of sulfur (S) has been recognized for both dry and wetland plants as a significant growth limiting factor. S-oxidizers enhance the oxidation rate of S and increase sulfate (SO4 − 2) production by making them available in critical growth stages, resulting in higher plant growth and yield. A two-phase study was undertaken to assess the effectiveness of microbial redox reactions on soil nutrient bioavailability and crop growth. In the first phase isolation of S bacteria was carried out while in the second phase, a pot experiment was conducted and these bacteria were evaluated as a nutrient source along with different ratios of NPK fertilizer by growing canola (Brassica napus) as a test crop. Treatment combinations were, viz., Control (no inoculum), ½ NPK fertilizer (50, 30, and 25 kg ha−1), Full NPK fertilizer (100, 60, and 50 kg ha−1), ½ NPK+SOB, ½  NPK+SRB and ½ NPK+SOB+SRB. Sulfur oxidizing bacteria (SOB) strains were isolated from samples and then screened based on pH reduction (in thiosulphate broth). Sulfur-reducing bacteria (SRB) are characterized by their anaerobic energy metabolism based on the dissimilatory reduction of SO4−2 to hydrogen sulfide (H2S) or S ° to be useful for SOB. Among different bacterial consortiums, the best results for nutrient bioavailability (macro- and micronutrient) in soil and plant the treatment ½ NPK+SOB+SRB compared to full NPK increased soil N, P, K, and SO₄ by 15.9%, 38%, 2.0%, and 72%, respectively. In plants, it boosted N, K, and SO₄ by 7.7%, 31%, and 239%, respectively. The greatest pH reduction (4%) was observed with ½ NPK+SOB relative to full NPK. This study demonstrates that microbial inoculation along with ½ NPK increases the bioavailability of macro- and micronutrients for crops.